Indonesian and Malaysian Labor Law Comparative Study In Enhancing The Competitiveness of Workers In The Framework of The Asean Economic Community - Emilia Fitriana Dewi; Dematria Pringgabayu; Kurnia Fajar Afgani; Yani Pujiwati; Isti Raafaldini Mirzanti (Journal Research of Social Science, Economics, and Management, 2022)
The Employment conditions have various labor problems ranging from wage policies, working time, occupational safety and health, social security and maternity protection, equality of opportunity and non-discrimination, and freedom of association, to the lack of employment opportunities and the increasing unemployment rate. Within the framework of the MEA, Indonesia and Malaysia need to develop labor institutions through the development of human resources in preparing competent workers according to the directives of the AEC blueprint. HR development can be carried out in accordance with the rule of law by preparing the workforce of each country at the ASEAN level. MEA facilitates the movement of skilled workers to be accepted in ASEAN member countries and the flow (in and out) of labor between ASEAN member countries is very open, for that there will be competition between countries in skilled labor.